INFLUENCE OF PHYSICAL AND HEAT PROCESSES ON THE STRUCTURE AND PROPERTIES OF HIGH-CHROMIUM CAST IRON DURING MACHINING - Netrebko, V. V. (Science and Transport Progress, 2014)
Purpose. Analysis of changes of high-chromium cast irons' structure and properties under the influence of physical and heat factors during mechanical machining. Methodology. The methodology of evaluation of the cutting tool's force and heat influence on the machined material has been developed and applied. Cast specimens underwent preliminary turning to obtain the diameter of 25 mm. The microsection was made on the end surface of the specimen with the length of 50 mm. Standard plates with sizes 10×10 mm made of VK8 according to the State Standard 19051-80 were used in the turning process. Findings. Force influence on the specimens made of highchromium cast iron caused strain hardening during machining. Temperature influence on the structure and properties of high-chromium cast iron during machining caused increase of the plasticity characteristics of the metallic base in the cutting area, fragmentation of the carbide phase and elimination of the strain hardening. During turning with cutting depth 0.8 mm only force influence of the cutting tool on the specimen took place. Carbide inclusions in the surface layer didn't undergo sufficient changes; at the same time the metallic base was strain-hardened to 1 100 HV50. As it was drawn away from the turning surface, the microhardness of the metallic base was decreasing and equaled to 500…520 HV50 at the distance of 1.2 mm from the turning surface. Strain hardening was not observed at the depth of more than 3mm. Cutting depth increase up to 1.5 mm caused simultaneous influence of force and heat factors. The temperature influence revealed in increasing of metallic base plasticity in the specimen's surface layers. Strain hardening of heated surface layers didn't occur. While drawing away from the cutting surface, the influence of the temperature factor decreased, when the influence of force factor remained the same. Due to the base plasticity decrease the strain hardening occurred. The metallic base strain was hardened to 490…520 HV50. The overall heating of the specimen caused the decrease of strain hardening depth to 0.4 mm. Originality. The methodology of change evaluation of high-chromium cast iron structure and properties under the influence of physical and heat factors during mechanical machining has been elaborated. Practical value. This methodology allows developing the recommendations for choices of highchromium cast iron machining modes and conditions.